A qualitative study of young drivers and deterrence based road policing. (May 2020) - Bates, Lyndel; Anderson, Levi; Rodwell, David; Blais, Etienne
Highlights: Classical deterrence theory has three elements: certainty, severity and swiftness. Geographical context affects the perceptions of certainty. Those from regional areas less likely to believe they will be caught breaking rules. Young drivers believe enforcement cameras increase the certainty they will be caught. Police agencies should take actions to increase perceptions regarding certainty. Abstract: Deterrence theory is the predominant theory used to underpin road policing initiatives. However, survey research indicates that this approach may not be as effective for young drivers. This study uses focus groups, conducted in both metropolitan and regional locations in two Australian states (Queensland and Victoria), to explore three components of classical deterrence theory: certainty, severity & swiftness. The results suggest that geographical context affected perceptions of certainty with individuals from regional locations less likely to indicate that they would be caught by police for committing a traffic offence. Additionally, the use of cameras to detect road offences increased perceptions of certainty for young drivers. The results of this study suggest that police agencies should focus on undertaking actions to increase the perceptions of certainty swiftness and severity of punishment, particularly in regional areas, for young drivers who engage in illegal behaviour on the road. Where appropriate, these actions should take into account the geographical context. There may also be value in considering augmenting deterrence theory with other theoretical perspectives for this group.